Teaching Collocations Using Modern Technologies - Rashidova Gulshoda Ilhomiddin qizi (Genius Publishing Group, 2022)
This article considers about using collocations with the help of modern technologies in EFL teaching. There are different opinions of scholars are analyzed and generalized in this field as well. This paper is aimed on the one hand, to get ELT instructors aware of the concept of collocations and its significance, for those who are not already aware of this aspect of language. On the other hand, the suggesting ways to help learners develop collocational knowledge.
Keywords: concept of collocations; collocational knowledge; collocational competence; language proficiency